Arqueologia de ambientes aquáticos no Egito: uma proposta de pesquisa das sociedades dos oásis do Período Faraônico - Costa, Márcia Jamille Nascimento (2013)
Although the societies that lived in Egypt during the interlude of Pharaonic Period can be defined by the way of life intrinsically linked to the aquatic environment, whether for subsistence, socializing or in a symbolic way, the archaeological sites are analyzed only from point of view of land, ignoring your surroundings. Consequently, the areas of oasis, located in the Western Desert, are also ignored about this type of research. The suggestion of this research is to propose the observation of societies Egyptian oasis of a aquatic viewpoint, independent of the Nile or the lakes of Libyan Desert, but not observed only as a place to collect resources, but a place used for socializing and inspiration to culture material. To understand the populations of oasis is necessary in first understand the populations of the Nile and his speeches, especially those related to its vision over what was the desert environment and consequently its inhabitants and how this implies in material culture, especially those related to aquatic territories.